Implementation of Tropical Cyclone Detection Scheme to CCAM model for Seasonal Tropical Cyclone Prediction over the Vietnam East Sea - Ha, Pham Thanh; Huy, Hoang Danh; Nam, Pham Quang; Katzfey, Jack; McGregor, John; Chi, Nguyen Kim; Duc, Tran Quang; Linh, Nguyen Manh; Van Tan, Phan (VNU Journal of Science: Earth and Environmental Sciences; Vol 35 No 3DO - 10.25073/2588-1094/vnuees.4384, 2019)
This study has selected a vortex tracking algorithm scheme for simulating the activity of tropical cyclone in the Vietnam East Sea by CCAM model. The results show that the CCAM model is able to simulate well the large scale in each month through a reasonable description of the movement rules of the tropical cyclone in the study area. Then, this vortex tracking algorithm scheme was applied to test the seasonal forecast with the outputs of the CCAM model with a resolution of 20km for September 2018 and October 2018. The obtaining results are forecasted quite closely in terms of both quantity and high potential occurrence areas of the tropical cyclone when compared with reality. In particular, for October 2018, although the activity area of ​​the tropical cyclone - YUTU is significantly different from the multi-year average activity position, the seasonal forecast results are obtained from the 120 members of the CCAM model captured this difference. This suggests that it is possible to apply the CCAM model in combination with the selected vortex tracking algorithm scheme for the seasonal forecast of the tropical cyclone over the Vietnam East Sea region in the future.